Comparison of the pregnancy outcomes and health indicators of newborns before and after the pandemic of covid-19 in Iran - Tahoora Hasanpoor Baghbani; Mina Jafari; Majid Mirmohammadkhani; Kamyar Mansori; Elahe Ghods (Preventive Care in Nursing and Midwifery Journal, 2024)
Background: COVID-19 originated from China and causes pneumonia and respiratory, digestive and many other symptoms. The risk of adverse pregnancy outcomes may increase in pregnant women infected with this virus. Objectives: This study aimed to compare the pregnancy outcomes and health indicators of newborn born in two periods before (the first 6 months of 2019) and after (the first 6 months of 2020) the COVID-19. Methods: In this cross-sectional study, 2303 newborns were studied. Of these, 1195 were born in the first 6 months of 2019 and 1108 were born in the first 6 months of 2020. The data collection tool was a checklist that was extracted from the integrated health system (SIB) of the Iranian Ministry of Health. The SPSS26 was used for data analysis. Results: The newborns born in these two periods before and after COVID-19 pandemic had no statistically significant differences in terms of maternal age, gestational age, birth weight, height and head circumference at birth (P-Value>0.05). There was no statistically significant difference in terms of gender, stillbirth and twins or multiples variables in the two time periods before and after COVID19 (P-Value>0.05). Cesarean section rate after the COVID19 pandemic in the first 6 months of 2020 (60.8 %) was higher than before pandemic in the first 6 months of 2019 (56.7 %) (P-Value<0.05). In addition, the birth rate in rural areas after the COVID-19 pandemic was higher than before pandemic (P-Value=0.005). Conclusion: Caesarean section rate after the COVID-19 pandemic has increased significantly compared to before